Trend of STEAM Research in Elementary Science Education: A Bibliometric Analysis - Nurul Annisa; Ikhlasul Ardi Nugroho; Sekar Purbarini Kawuryan; Putri Nurhaliza (Postgraduate, University of Mataram, 2025)
This bibliometric analysis examines research trends in STEAM (Science, Technology, Engineering, Arts, Mathematics) in primary school science education based on articles indexed in Scopus from 2016 to 2025. The research method employed bibliometric analysis using Publish or Perish and VOSViewer software to map productivity, author collaboration, and geographical distribution. The results show a significant increase in publications since 2019, with the United States as the leading contributor. The research focus has shifted from developing the STEAM concept towards evaluating the effectiveness of its implementation, particularly during the COVID-19 pandemic. This study identifies a gap in evaluative research on the impact of STEAM on learning outcomes and student engagement. The conclusion emphasizes the need for further studies that integrate impact analysis to strengthen the adaptation of the STEAM approach in education.